Alcohol-impaired driving enforcement priorities and strategies in a nationwide sample of U.S. law enforcement agencies. (2nd January 2023) - Scholz, Natalie; Lenk, Kathleen M.; Erickson, Darin J.; Toomey, Traci L.; Jones-Webb, Rhonda; Nelson, Toben F.
Abstract: Objective: Excessive alcohol consumption leads to a range of public health problems and social and financial burdens. Traffic crashes resulting from alcohol-involved driving are a major contributor to the overall health consequences of alcohol. Various laws and enforcement strategies aim to prevent alcohol-involved driving. The extent to which law enforcement agencies prioritize enforcement of alcohol-impaired driving laws can help to reduce alcohol-impaired driving. Among law enforcement agencies in the US, we examined prioritization of alcohol-impaired driving enforcement and how it is associated with use of specific enforcement strategies, as well as agency and community characteristics. Methods: We conducted a survey of a national sample of 1, 024 US police and sheriff agencies in 2019. We assessed prioritization of alcohol-impaired driving enforcement, use of specific enforcement strategies (saturation patrols, sobriety checkpoints, open container law enforcement, training field officers to identify driving impairment), and agency and jurisdiction characteristics. We assessed how priority of enforcement (high vs. low) was associated with use of specific strategies, and agency and jurisdiction characteristics using regression models that accounted for agencies nesting within states. Results: A majority of agencies (68%) placed a high priority on alcohol-impaired driving enforcement. Almost all agencies (93%) reported performing at least one alcohol-impaired driving enforcement strategy and the most common strategy used was saturation patrols. Agencies that prioritized alcohol-impaired driving enforcement were more likely to use sobriety checkpoints and saturation patrols, conduct enforcement of open container laws and train field officers in identifying driving impairment (p < 0.05). They were also more likely to have an officer assigned primarily to alcohol enforcement, have an alcohol division, and serve jurisdictions that had fewer Black residents (p < 0.05). Conclusions: Many law enforcement agencies utilize strategies to address alcohol-impaired driving, however, some strategies are underutilized and an opportunity exists for agencies to incorporate additional strategies to help prevent alcohol-impaired driving. Agencies that made alcohol-impaired driving enforcement a priority were more likely to conduct related enforcement strategies. Encouraging police and sheriff agencies to prioritize alcohol-impaired driving enforcement may be an effective approach for preventing alcohol-related harms.